(untitled) (Journal of Plant Disease Sciences, 2017)
The present investigation was related to find out the diversity in Bacillus citrus rhizosphere. The research survey entitled " Diversity Analysis in Bacillus Citrus Rhizosphere Soil" was carried out at Hingna tahsil of Nagpur district in the month of September, 2014. Soil contains bacterial count ranged from 36×10 to 3 53×10 cfu g in low yielding soils while 45×10 to 108×10 cfu g in optimum 3 -1 3 3 -1 yielding and 86×10 to 132×10 cfu g in high yielding citrus rhizosphere, 3 3 -1 Bacillus subtilis Bacillus polymyxa count ranged from 8×10 to 33×10 cfu g , ranged from 3 3 -1 2×10 to 12×10 cfu g . ranged from 4×10 to 23×10 cfu g . 3 3 -1 3 3 -1 Bacillus licheniformis Bacillus mycoides Bacillus pumilus ranged 8×10 to 39×10 cfu g . ranged from 3 3 -1 1×10 to 11×10 cfu g and count ranged 6×10 to 14×10 cfu g . 3 3 -1 3 3 -1 Bacillus cereus